Translating and publishing antiquity literary works in Lithuanian - Stonienė, Vanda (Knygotyra, 1988)
The paper presents an attempt to analyze in a statistical way the publications of Greek and Roman antiquity literature in Lithuanian from their beginnings in the 18th century.The translation of antiquity literature into Lithuanian began with the publication of Aesop's fables in Königsberg in 1706. During the 19th century, Lithuanian enlighteners (especially S. Daukantas) took a keen interest in ancient Greek and Roman literature. They compiled dictionaries, wrote grammars, and translated several ancient literary works. Unfortunately, not all of them could be published at that time. Moreover, towards the turn of the century, under the tsarist imposition of the ban on Lithuanian press, the publication of ancient authors stopped almost entirely. Later, between 1919 and 1940, eleven antiquity writers were published (a total of 28 works in 2,000-5,000 copies each).During 1947-1985, under favorable cultural conditions, 36 works of ancient writers, 12 collections of their works, and some reading books were issued. Average editions of these were usually 10,000-15,000 copies, but some (e.g., "Odyssey") amounted to 30,000 copies. Topical information, biographical and bibliographical data concerning individual Greek or Roman authors and their works, glossaries, and commentaries are characteristic features of the publications from the last four decades. The typographical appearance of these books has been greatly improved compared to previous Lithuanian editions of ancient literature.
Keywords: -